Implementación de una planta recicladora de neumáticos sin uso y procesadora de grano de caucho reciclado en la ciudad de Loja - Lañon Vega, John Fernando (2019)
Through the present research project that aims to determine the feasibility for the: "IMPLEMENTATION OF A RECYCLING PLANT WITHOUT USE AND PROCESSOR OF RECYCLED RUBBER IN THE CITY OF LOJA", which took into consideration the use of specific objectives such as: market study, technical study, legal-administrative study and economic-financial study, which allowed us to obtain the conclusions. In the market study it was possible to determine that the main clients of the product will be the owners of the synthetic courts, and through the analysis of the demand and the supply it was possible to identify an unsatisfied demand of 14,457 pounds of recycled rubber grain, since in the city of Loja there are no companies dedicated to this activity. The results of the technical study made it possible to identify the capacity used by the company, which will be 323,000 pounds of recycled rubber grain for year one. In addition, the ideal place was determined for the location of the plant that is in the industrial park located in the Amable Maria neighborhood of the parish of the valley of the city of Loja, located on Salvador Bustamante Celi Avenue 600 meters from the Military College Lieutenant Colonel Lauro Guerrero, North Sector. The legal-administrative study indicates the minute of constitution, in addition the administrative levels were established which allowed to elaborate the organization charts of the company and the Manueles of functions. The analysis of the economic-financial study determines that the plant requires an investment of $84,258.64, which will be financed through the contribution of investors, who will contribute $54.258.64 dollars, which is equivalent to 64.40% of the total investment and the other 35.60% will be financed by bank loan, through the budget we obtained a Total Production for the year of $94.699,36, which gives us a Unit Production Cost of $0.29 to which we add a profit margin of 40%, obtaining a Unit Sales Price of $0.41 multiplied by 323.000.The elaboration of the Profit and Loss Statement shows that for the first year of operations there is a Net Profit of $21.733,50; the Cash Flow for the first year gives a cash flow of $26,386.64; through the financial evaluation the following indicators were analyzed: Net Present Value which is $90.313.02 which shows that the project is feasible since the NPV exceeds the value of the investment, the Internal Rate of Return which is 35.40%, the Cost Benefit Ratio indicator shows that for each dollar invested the company earns 0.39g ctvs, the Capital Recovery Period shows that the investment will be recovered in 3 years, 11 months and 26 days, the sensitivity analysis shows that the product is not sensitive to the 26.43% increase in costs and the 16.50% decrease in revenues. According to the above mentioned, it is determined that the project is feasible in terms of Market, Technical, Legal, Administrative and Economic-Financial Study.